Clade Ib: a new emerging threat in the Mpox outbreak - Srivastava, Shriyansh; Laxmi,; Sharma, Khyati; Sridhar, Sathvik Belagodu; Talath, Sirajunisa; Shareef, Javedh; Mehta, Rachana; Satapathy, Prakisini; Sah, Ranjit (Frontiers in Pharmacology, 2024)
• Mpox clade Ib accelerates with contact and sexual transmission, putting children, immunocompromised people, and sex workers at risk.• Due to genetic alterations, Mpox transmission has risen, requiring robust infrastructure for early identification and effective antiviral therapy.• AI improves surveillance, diagnosis, and optimization for clade Ib outbreaks; data analysis identifies hotspots for greater precision and effectiveness.• Lessons learned from COVID may reduce healthcare burden and stabilize economies, particularly in low-resource countries.